Rising groundwater table due to restoration projects amplifies earthquake induced liquefaction risk in Beijing - Yuan Li; Rui Wang; Hongbo Ma; Jian-Min Zhang (Nature Communications)
Abstract Groundwater restoration is increasingly common to mitigate groundwater overexploitation, which proves effective in resolving urban water scarcity and regional unsustainable development. China’s South-to-North Water Diversion Project is one of the largest water transfer projects to restore groundwater and resolve water shortage in Beijing. However, how the rapidly restored groundwater of this magnitude changes regional seismic stability is largely unknown. Here, we explore the relation between elevated groundwater table and seismic ground liquefaction based on the case of Beijing under the impact of the South-to-North Water Diversion Project. We collect groundwater table depth records and use them to drive three-dimensional geotechnical models that generate ground liquefaction hazard maps. We find a remarkable increase in coverage and severity of liquefaction due to groundwater table rise. Infrastructures built during the rapid urbanization process are often under low groundwater table and thus illy prepared for this increased seismic risk. These findings highlight the necessity to consider the seismic consequence of large-scale groundwater restoration projects.